On farm characterization of Horro cattle breed production systems in western Oromia, Ethiopia - Mekonnen, A.; Haile, Aynalem; Dessie, Tadelle; Mekasha, Yoseph (2012)
he survey was carried out in Horro district of Horro Guduru zone, west part of Ethiopia. The objectives of the survey were: to describe cattle production system, trait preferences, breeding practices, and constraints in utilization of the breed and to use the information generated as baseline data to design breeding strategy of the breed. Data were collected through in-depth interviews, group discussions and secondary data collections from different sources. Statistical Package for Social Science was employed to analyze data. Horro cattle are kept in a mixed crop-livestock production system and are the dominant livestock species in the area. Cattle have multi-functional roles in the production systems. Among reason of keeping cattle, draught power was ranked first followed by milk production. Farmers prefer composite traits from their male and female cattle. Draught power performance, body size, hump size, adaptability and coat color were among the higher ranked preferred traits for male cattle in that order. Preferred traits for female cattle include milk yield, fat yield, calving interval, adaptability and coat color.